(untitled) (Plant Tissue Culture and Biotechnology, 2026)
The gold-spotted, brackish water fish, scientifically known as Coilia dussumieri, is widely consumed in Bangladesh, both fresh and dried. This study employed both traditional and molecular methods to detect the fungal species associated with dried C. dussumieri. The properties of fungal mycelial growth were also studied. Curvularia moringae was identified in the selected dried fish, which are often consumed in Bangladesh. It was molecularly identified using a 593 bp PCR product from the internal transcribed spacer (ITS) region. The molecular phylogenetic tree revealed that the examined fungus has 100% sequence similarity to the C. moringae species complex. The results of the study on the impact of culture media on the mycelial growth and development of C. moringae were evaluated. C. moringae mycelial growth was highest (81.33 mm) in the potato dextrose agar (PDA) medium, followed by (66.25 mm) in potato sucrose agar (PSA), (47.16 mm) in glucose peptone agar (GLP), (40.25 mm) in Hoppkins, and (35.12 mm) in yeast extract agar medium. C. moringae thrived and matured optimally at 25°C and pH 6.0. As far as we know, the experimental identification of the dry fish fungus C. moringae from C. dussumieri is the first to be reported in Bangladesh using both traditional and molecular approaches. Plant Tissue Cult. & Biotech. 36(1): 129-138, 2026 (June)